MAKLUMAT INDUSTRI DAN SAINS INFORMATION SERVICE FOR COMMERCE & INDUSTRY - Perpustakaan, Hamzah Sendut (Perpustakaan Universiti Sains Malaysia, 2003)
MALAYSIA TO RESTRATEGISE DUTY FREE CRUDE PALM OIL EXPORT TO INDIA Malaysia has to restrategise its duty free crude palm oil export to India in the future. India was a big buyer with 3.5 million tonnes of palm oil annually of which 50 percent came from Malaysia. There are discriminatory tariffs that had been imposed on palm oil as compared to soyabean oil. Currently, the tariffs imposed on crude palm oil is 65 percent while crude soyabean oil is 45 percent.